2020
DOI: 10.1002/smll.202001516
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicology: The Need for a Human Touch?

Abstract: With the ever‐expanding number of manufactured nanomaterials (MNMs) under development there is a vital need for nanotoxicology studies that test the potential for MNMs to cause harm to health. An extensive body of work in cell cultures and animal models is vital to understanding the physicochemical characteristics of MNMs and the biological mechanisms that underlie any detrimental actions to cells and organs. In human subjects, exposure monitoring is combined with measurement of selected health parameters in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 114 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…Several studies have searched for the most useful biomarkers of oxidative damage in humans [1][2][3][4][5], and it has been shown that no single marker may be satisfactory [6,7]. The need for nanotoxicology studies in humans is considered vital due to the potential damage to cells, organs, and organisms, and to a lack of human data, especially in occupational settings [8,9], where the exposure is the highest. Consumer product usage, such as sunscreen, may also be cause for concern, as absorption of nanoparticles through the skin was found [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have searched for the most useful biomarkers of oxidative damage in humans [1][2][3][4][5], and it has been shown that no single marker may be satisfactory [6,7]. The need for nanotoxicology studies in humans is considered vital due to the potential damage to cells, organs, and organisms, and to a lack of human data, especially in occupational settings [8,9], where the exposure is the highest. Consumer product usage, such as sunscreen, may also be cause for concern, as absorption of nanoparticles through the skin was found [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, for a practical use on nanoantioxidants, this list must be integrated with toxicological and environmental considerations [119], that go beyond the aims of this review [120]. Nevertheless, we believe that the use of these guidelines will inspire the research of novel nanomaterials able to cope with the autoxidation of organic materials in fields spanning from foods to plastic to biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation is a prime exposure route for humans and the respiratory epithelium is the first tissue that inhaled substances come in contact with. [21] To date, no in vitro models have been accepted by regulatory agencies as a complete replacement for inhalation toxicity testing in animals. In animal models, acute inhalation toxic-ity testing for regulatory purposes in rats or mice is done according to OECD TG403, TG436, and TG433 test guidelines.…”
Section: Perspective Of In Vitro Alternatives To Acute Inhalation Toxicity Studies In Animal Modelsmentioning
confidence: 99%